A prototype model for continuous agriculture field monitoring and assessment - Bhimanpallewar, Ratnmala; Rama Narasingarao, Manda (International Journal of Engineering and Technology, 2018)
Indian farmers are totally dependent on agriculture and livestock for satisfying their basic food and economical needs. Maximum farmers are habitual to take crops continuously with traditional ways without checking the current suitability. Government of India has developed centers to train and provide the information to farmers but everyonedon't approach to it. To get the increased yield, usually farmers add fertilizers without understanding requirement which may leads to soil degradation.Proposed solution is an automated system which can monitor major parameters required to estimate suitability for cropping. This system can be made available locally to every farmer. Outcome of this monitoring system can be used to identify particular crop suitability, so that suitable crop can be adopted.